Teleworking and Telestudy in Generation Z of Peru: Proposals for the Management of ’Homenization’ Behavior - Canales Cuba, Roxana Jacqueline; Genoud, María Andrea (Cuadernos de Administración, 2025)
Generation Z’s entry into the workforce occurred alongside the onset of confinement due to the COVID-19 pandemic. The present study has two objectives: first, to describe how the pandemic affected the working, academic and personal activities of this generation; second, to explore the future expectations of the work of this cohort. On the basis of a phenomenological perspective of a qualitative nature, an exploratory and descriptive study was carried out using an interview guide developed from the Diagnostic Tool for Enriching Labor Functions (HDEFL), adapted in Latin America, which allows companies to diagnose management measures, articulating the worker’s profile with the characteristics of each job (including motivational, social and context variables) to stimulate work results in terms of three dimensions: behavior, attitude and well-being. The results show that, to carry out teleworking and telestudy as a sustainable practice, seven key competencies are necessary for this generational group: organization and time management, adaptation to unforeseen events with resilience, digital communication, technological patience, ability to ask questions, commitment to objectives and performance indicators, and autonomy for self-learning. Similarly, four thematic axes have been determined that companies must address so that this modality serves as a strategy to attract and retain human capital.